Tiltmeter Data Revealing Transient Magma Viscosity Changes During Eruptions - David Gomez-Ortiz; Jose Arnoso; Silvia Martín-Velázquez; Tomás Martín-Crespo; Fuensanta González Montesinos; Emilio Vélez; Maite Benavent (Remote Sensing)
Volcanic processes related to episodes of inflation, dike propagation, effusive activity, etc., can be detected by continuous surface tilt measurements. The interpretation of these measurements helps comprehend medium-to-short-term precursors of volcanic eruptions or establishes early warning alerts. Additionally, studying the transport and evolution of magmas from the Moho to the crust is key to understanding the eruptive process, but to date, they have not been traced from surface tilts. In this work, we witnessed two relevant and unique dynamic eruptive processes, as revealed by tilt signals, both in the 2021 La Palma eruption and in the 2011–2012 El Hierro eruption (Canary Islands). On the one hand, magma injection from the reservoir at depth is controlled by a pressure gradient. On the other hand, changes in magma viscosity, resulting from pressure variations, have been revealed from cyclic tilt signals. In the case of these signals, matching with a physical model helped us decipher them and establish the duration of this magmatic process, which varied depending on the size and rheological properties of the respective magma plumbing systems.